2017
DOI: 10.1111/gcb.13705
|View full text |Cite
|
Sign up to set email alerts
|

Biomass responses in a temperate European grassland through 17 years of elevated CO2

Abstract: Future increase in atmospheric CO concentrations will potentially enhance grassland biomass production and shift the functional group composition with consequences for ecosystem functioning. In the "GiFACE" experiment (Giessen Free Air Carbon dioxide Enrichment), fertilized grassland plots were fumigated with elevated CO (eCO ) year-round during daylight hours since 1998, at a level of +20% relative to ambient concentrations (in 1998, aCO was 364 ppm and eCO 399 ppm; in 2014, aCO was 397 ppm and eCO 518 ppm). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 55 publications
(94 reference statements)
1
51
0
Order By: Relevance
“…Theoretical analyses further suggest that plant community composition may be a potential mediator of CFEs under multifactorial global change (Kardol et al 2012;Langley & Hungate 2014), partly due to the diverse CO 2 responses of photosynthesis among plant species and related variations in interspecific competition (Poorter & Navas 2003). For example, growth stimulation of C 3 forbs under eCO 2 is higher than that of C 3 /C 4 grasses in two FACE experiments (Lee et al 2011;Newton et al 2014), in contrast to other work Andresen et al 2017). In addition, a 20-year FACE experiment has revealed that eCO 2 can promote growth of C 3 grasses greater than C 4 grasses during the first 12 years of treatment, but the pattern reverses during the subsequent 8 years .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Theoretical analyses further suggest that plant community composition may be a potential mediator of CFEs under multifactorial global change (Kardol et al 2012;Langley & Hungate 2014), partly due to the diverse CO 2 responses of photosynthesis among plant species and related variations in interspecific competition (Poorter & Navas 2003). For example, growth stimulation of C 3 forbs under eCO 2 is higher than that of C 3 /C 4 grasses in two FACE experiments (Lee et al 2011;Newton et al 2014), in contrast to other work Andresen et al 2017). In addition, a 20-year FACE experiment has revealed that eCO 2 can promote growth of C 3 grasses greater than C 4 grasses during the first 12 years of treatment, but the pattern reverses during the subsequent 8 years .…”
Section: Introductionmentioning
confidence: 85%
“…; Andresen et al . ). In addition, a 20‐year FACE experiment has revealed that eCO 2 can promote growth of C 3 grasses greater than C 4 grasses during the first 12 years of treatment, but the pattern reverses during the subsequent 8 years (Reich et al .…”
Section: Introductionmentioning
confidence: 97%
“…The grassland has not been ploughed for at least 100 years, being managed as a hay meadow with two cuts per year, with granular mineral calcium‐ammonium‐nitrate fertilizer applied at the rate of 40 kg N ha −1 year −1 in mid‐April. Before 1996, fertilizer was applied at a rate of 50–100 kg N ha −1 year −1 (Andresen et al., ; Kammann et al., ). Meteorological data were available from meteorological stations at the field site.…”
Section: Methodsmentioning
confidence: 99%
“…Three equally sized control plots were maintained at ambient atmospheric CO 2 levels (aCO 2 ). The soil of the study site is classified as a Fluvic Gleysol (FAO classification) with a sandy clay loam texture overlying a subsoil clay layer (J€ ager et al, 2003 (Andresen et al, 2017;Kammann et al, 2008). Meteorological data were available from meteorological stations at the field site.…”
Section: Study Site and Designmentioning
confidence: 99%
See 1 more Smart Citation